Zagadnienia turystyczne w dokumentach planistycznych w aspekcie uwarunkowań przyrodniczych gmin powiatu poznańskiego - Poniży, Lidia (My University, 2009)
Recreation grounds which city residents have at their disposal enhance their living conditions and improve the quality of life. The provision of short-term (after-hours) and weekend recreation is one of the major tasks of the suburban zone. However, an uncontrolled spread of Poznań into areas attractive in recreational terms may mean their irreversible loss. The fast rate of absorption of suburban areas by the city, especially those of high natural and cultural value, calls for measures protecting them against investment, so as to help them maintain their recreational function both today and in the future. What can secure Poznań's suburban areas against detrimental effects of suburbanisation is proper space management. Given the investment pressure and a great demand for new building lots, this is sometimes a very difficult task. Maintaining old and establishing new recreation grounds in communes is only possible through the adoption of suitable provisions in planning documents. Such decisions can crucially affect the operation of recreation space around Poznań. Therefore, an analysis was made of tourism-related issues addressed in selected planning documents in terms of direct and indirect provisions concerning recreation and leisure. (Direct provisions include, e.g., the delineation of recreation grounds, while indirect ones concern the rules of protection of the environment, nature and cultural landscape, or prospects of transport development.) The analysis embraced 12 communes neighbouring on Poznań and forming its suburban zone.
Natural conditions and tourist issues in the planning documents of selected communes of Poznań poviat
Keywords: zagospodarowanie przestrzenne; spatial development